Arrangements versus Agreements: Evaluating two approaches to measuring male couples’ rules and understandings around sex with outside sex partners - Dellucci, Trey V. (Arch Sex Behav, 2020)
One-to-two thirds of new HIV infections among sexual minority men occur within the context of main partnerships. This has led to increasing attention to the rules and boundaries male couples form around sex with outside partners as a mechanism to manage HIV risk. These rules and boundaries have generally been operationalized either as a sexual agreement – the decisions couples make together about their sexual boundaries with outside partners – or a sexual arrangement – how couples handle sex outside the relationship, which may or may not involve an implicit or explicit consensus between partners. The goal of the current study was to examine the correspondence of these two approaches to the operationalization of rules and boundaries. Additionally, the study tested whether agreements and arrangements were differentially associated with dyadic communication and sexual behavior with casual partners. Results indicated a high level of correspondence among assessment methods. Similarly, patterns of sexual behaviors with casual partners were consistent across both sexual agreements and sexual arrangements. In contrast, patterns of communication varied as a function of assessment type. Specifically, constructive, avoidant, and sexual communication varied across sexual agreement types; whereas sexual arrangement types only differed with respect to constructive communication. These findings suggest that there is substantial overlap between arrangements and agreements. Findings particularly related to associations with sexual behavior may largely generalize across these methods of operationalization. In contrast, survey-reported sexual agreements were a more sensitive correlate of dyadic communication.